ПРОСТОРОВА ОЦІНКА РОЗПОДІЛУ КОНЦЕНТРАЦІЇ ХЛОРОФІЛУ «А» УКРАЇНСЬКОГО СЕКТОРУ ПІВНІЧНО-ЗАХІДНОЇ ЧАСТИНИ ЧОРНОГО МОРЯ - Соколов, Є.В. (Marine Ecological Journal, 2023)
Using geoinformation systems, a spatial-statistical analysis of chlorophyll-a concentration distribution was conducted based on satellite observations in the waters of the northwestern part of the Black Sea during different hydrological years. The temporal dynamics of chlorophyll-a concentrations, associated with the influence of river discharge and other factors, were examined. Utilizing the databases of international online platforms, namely Copernicus Marine Service (CMEMS), Giovanni – NASA, Copernicus Climate Change, and the analytical capabilities of the ESA SNAP software platform, correlations were identified between chlorophyll-a concentration, water temperature, insolation, and phosphate concentration, representing the comprehensive dynamics of aquatic ecosystems in the region. Spatial anomalies of concentrations were calculated based on statistical boundaries of mean values and standard deviations. Spatial zoning of the water area was performed to identify areas at high risk of eutrophication using statistical analysis, including within the boundaries of national water bodies classified according to the EU Water Framework Directive and Marine Strategy Framework Directive ideologies. The study also included an analysis of the spectral characteristics of the sea surface, particularly the light reflection coefficient, based on Sentinel-3 (OLCI) satellite imagery. Using the bio-optical processor “Case 2 Regional Coast Colour (C2RCC)”, the relationship between chlorophyll-a concentration and light reflection in different spectral ranges was studied. It was found that seawater with varying chlorophyll-a concentrations exhibits different spectral profiles. The long-term distribution of dissolved oxygen in the bottom layer was investigated based on the hydrodynamic model “Black Sea Biogeochemistry Analysis and Forecast” from the international service CMEMS, aiming to identify the most vulnerable areas to the influence of eutrophication processes under conditions of vertical stratification by water density.